Fully Intra-articular Lasso-Loop Stitch Technique for Arthroscopic Anterior Talofibular Ligament Repair. (March 2022) - Qin, Jiajun; Fu, Qiang; Zhou, Qing; Wu, Helin; Zhi, Xiaosong; Xu, Feng; Cai, Xianhua; Wei, Shijun
Background: Arthroscopic techniques have gradually become popular for anterior talofibular ligament (ATFL) repair. However, the reliability of the repair and the risk of nerve injuries are of concern. The aim of this study was to evaluate the fully intra-articular lasso-loop stitch technique for arthroscopic ATFL repair. Methods: From October 2018 to December 2019, 43 cases with chronic lateral ankle instability were treated with this fully intra-articular lasso-loop stitch technique using the Arthro-Pierce instrument. The Karlsson-Peterson score, Cumberland Ankle Instability Tool (CAIT) score, visual analog scale (VAS) score, anterior drawer and talar tilt stress fluoroscopy were evaluated at the preoperative and final follow-up appointments, respectively. All surgical complications were also recorded. Results: A total of 39 cases were followed up for a mean of 28.23 ± 3.64 months (range, 23-34 months). At the final follow-up, the averages of the Karlsson-Peterson, CAIT and VAS scores were 90.26 ± 6.58, 88.56 ± 7.21 and 0.79 ± 1.06, respectively. During surgery, 2 cases were modified with augmentation of the inferior extensor retinaculum. No nerve injuries were encountered. Only 1 female complained about mild knot irritation. A 25-year-old solider required revision surgery due to an accidental injury. Conclusion: We found the fully intra-articular lasso-loop stitch technique for ATFL repair using the Arthro-Pierce instrument to be reliable and safe with a sufficient and good-quality ligament remnant. Level of Evidence: Level IV, retrospective case series.